Implementing PIRLS in two languages: a New Zealand perspective - Chamberlain, Megan; Bennett, Hannah (Frontiers in Education, 2025)
As a former British colony, New Zealand is most often viewed as an English-speaking nation. While accurate, this descriptor does not provide insight into New Zealand’s post-colonial history and the attempts starting late last century to address the injustices associated with colonization. Monitoring of many policies and programs designed to address educational inequities use evidence from New Zealand’s national monitoring program and evidence from international large-scale assessments such as the IEA’s Progress in International Reading Literacy (PIRLS). PIRLS is the only large-scale study that regularly assesses New Zealand students in two languages—English and the Indigenous people’s language Māori. To adhere to the study’s standardized procedures, particularly around participation, the authors give their perspective on how implementing PIRLS in an indigenous language has evolved over the past 20 years. As context, the authors present a precis of New Zealand’s current educational context, including an introduction to Māori Medium Education which involves a small but critical sector charged with revitalizing an endangered language. The discussion also highlights some challenges associated with engaging an education sector for which the study appears to have little utility. It is envisaged that New Zealand’s experience serves as an example of a post-colonial country that is balancing the need for and wanting to be educationally inclusive, and whether this extends to an ILSA such as PIRLS to meet the study’s rigorous participation standards.